Development of an augmented reality e-module using problem-based learning to enhance science literacy and digital literacy - Yelykha Henirayuza Nst; Nur Aeni Ariyanti (University of Muhammadiyah Malang, 2025)
The limited use of effective teaching materials and learning models has hindered students' development of literacy competencies. This study aimed to develop and validate an augmented reality (AR)-based e-module integrated with the Problem-Based Learning (PBL) model to enhance students' science literacy and digital literacy. The research employed the ADDIE development model, involving validation by expert lecturers and practitioners, followed by implementation among 11th-grade students at SMA Negeri 1 Kampar Timur. The experimental design used a pretest–posttest equivalent control group design, with Class XI.5 assigned as the experimental group and Class XI.6 as the control group, via cluster random sampling. Data were collected using interviews, needs analysis questionnaires, expert validation instruments (for content and media), teacher and student practicality assessments, science literacy tests, and digital literacy questionnaires. Quantitative data were analyzed using the N-Gain and MANOVA tests to determine the e-module's effectiveness. The findings demonstrated that the AR-based e-module was valid and practical for classroom use and effectively improved students' science and digital literacy skills.